Omics-based analysis of honey bee (Apis mellifera) response to Varroa sp. parasitisation and associated factors reveals changes impairing winter bee generation - Kunc, Martin; Dobeš, Pavel; Ward, Rachel; Lee, Saetbyeol; Čegan, Radim; Dostálková, Silvie; Holušová, Kateřina; Hurychová, Jana; Eliáš, Sara; Pinďáková, Eliška; Čukanová, Eliška; Prodělalová, Jana; et al. (Insect biochemistry and molecular biology, 2023)
The extensive annual loss of honey bees (Apis mellifera L.) represents a global problem affecting agriculture and biodiversity. The parasitic mite Varroa destructor, associated with viral co-infections, plays a key role in this loss. Despite years of intensive research, the complex mechanisms of Varroa - honey bee interaction are still not fully defined. Therefore, this study employed a unique combination of transcriptomic, proteomic, metabolomic, and functional analyses to reveal new details about the effect of Varroa mites and naturally associated factors, including viruses, on honey bees. We focused on the differences between Varroa parasitised and unparasitised ten-day-old worker bees collected before overwintering from the same set of colonies reared without anti-mite treatment. Supplementary comparison to honey bees collected from colonies with standard anti-Varroa treatment can provide further insights into the effect of a pyrethroid flumethrin. Analysis of the honey bees exposed to mite parasitisation revealed alterations in the transcriptome and proteome related to immunity, oxidative stress, olfactory recognition, metabolism of sphingolipids, and RNA regulatory mechanisms. The immune response and sphingolipid metabolism were strongly activated, whereas olfactory recognition and oxidative stress pathways were inhibited in Varroa parasitised honey bees compared to unparasitised ones. Moreover, metabolomic analysis confirmed the depletion of nutrients and energy stores, resulting in a generally disrupted metabolism in the parasitised workers. The combined omics-based analysis conducted on strictly parasitised bees revealed the key molecular components and mechanisms underlying the detrimental effects of Varroa sp. and its associated pathogens. This study provides the theoretical basis and interlinked datasets for further research on honey bee response to biological threats and the development of efficient control strategies against Varroa mites.
Keywords: Proteomic; Varroidae; Gene Expression Profiling; proteomika; Smell; transkriptom; Transcriptomic; Metabolomic; Transcriptome; Proteomics; zvířata; Varroa destructor; včely; stanovení celkové genové exprese; čich; Honey bee; Bees; Infestation; Animals